Time course changes in hand grip strength performance and hand position sense in climbing - Matsouka, O.; Nani, S.; Papadimitriou, K.; Astrapellos, K.; Beneka, A.; Malliou, P. (Journal of Human Sport & Exercise, 2020)
The aim of the present study was to determine the time course changes in hand grip strength performance and hand position sense in novice climbers after one bout of two minutes continuing climbing on an artificial vertical wall. In addition, the rate of perceived fatigue of the participant felt right after the trial was recorded. Sixty five novice climbers aged 20 to 22 years (age 20.50± 0.65 years), were randomly assigned into two training groups with different tests protocols, the Grip strength test group (n=23), versus Joint position sense test group (n=14), and two control groups (n=14 each). The training protocol included one bout of two minutes continuing climbing on an artificial wall for both training groups whereas the control groups did not receive any kind of training during the study. Subjects were pre and post-tested for the selected variables. Statistical analysis showed that the grip strength was significantly decreased only for the training group F(6,216) = 30.460, p < .0005, partial Eta2 = .489. Similarly, the rate of perceived exertion changed significant F(2,563, 41,001) = 24.397, p < .0005, partial Eta2 = 0.604, with the training group to be more tired than the control after two minutes continuing climbing. Also, the wrist position sense of training group significantly deteriorated at post-test with F(3,78)=2,977, p<.05, partial Eta2 = .103. In conclusion, the performance of novice climbers is affected by hand grip strength performance and joint position sense of the hand. In addition it was required almost ten minutes of rest for partial recovery. These variables can be addressed through training design giving attention to those physical abilities.